Construction of Discipline of Madrasah Ibtidaiyah Students in PPKn Subjects - Fradila, Noveria; Dahlan, Zaini (Universitas Pendidikan Ganesha, 2023)
Character education is expected to be the main foundation in the success of a golden generation that is noble, moral, ethical, cultured and civilized based on the Pancasila philosophy. One of the character values that need to be developed is the value of discipline. Discipline character values are very important for students to have other good character values. Discipline is the right way to help students learn to live with good and useful habits. This paper aims to analyze the disciplinary construction of elementary school students in civics subjects. This type of research uses field research with a qualitative descriptive approach, namely a research process that produces descriptive data either in the form of writing or expressions obtained directly from the research field. Data collection techniques were carried out by means of observation, interviews and documentation. Based on the results of research on the Disciplinary Construction of Madrasah Ibtidaiyah Students in Civics Subjects that there are still some students who must be given affirmation regarding the level of discipline, while other students who are able to work well together and follow the applicable rules can change the teaching and learning process to be more conducive and directed through daily habits.